2003
DOI: 10.1124/mol.64.5.1145
|View full text |Cite
|
Sign up to set email alerts
|

An N-Terminal Histidine Is the Primary Determinant of α Subunit-Dependent Cu2+Sensitivity of αβ3γ2L GABAAReceptors

Abstract: Copper (Cu 2ϩ ) is a physiologically important cation and is released from nerve terminals. Cu 2ϩ modulates GABA A receptor currents in an ␣ subunit subtype-dependent manner; ␣1␤3␥2L receptors are more sensitive to Cu 2ϩ than ␣6␤3␥2L receptors. We compared the effect of Cu 2ϩ on ␣␤3␥2L receptors containing each of the six ␣ subtypes and generated ␣1/␣6 chimeras and mutants to determine the functional domain(s) and specific residues responsible for ␣ subtype-dependent differences in Cu 2ϩ sensitivity. Whole-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Copper can be found in different parts of CNS and it is accumulated in brain as other physiological metals, such as zinc, with relative importance for synaptic mechanisms (Kim and Macdonald, 2003). It has been known that copper concentrations in cerebrospinal fluid have been estimated to be around 70 М and the normal extracellular copper concentrations in brain ranged from 0.2 to 1.7 М (Mathie et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Copper can be found in different parts of CNS and it is accumulated in brain as other physiological metals, such as zinc, with relative importance for synaptic mechanisms (Kim and Macdonald, 2003). It has been known that copper concentrations in cerebrospinal fluid have been estimated to be around 70 М and the normal extracellular copper concentrations in brain ranged from 0.2 to 1.7 М (Mathie et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The genome of this fish shares many similarities with the human genome (Barbazuc et al, 2000). Ionotropic P2X receptors have already been identified and characterized in this specie (Kucenas et al, 2003) and GABAergic neurons were described in adult zebrafish brain (Kim and Macdonald, 2003). Studies have recently demonstrated the presence of NTPDases (Rico et al, 2003) and ecto-5 -nucleotidase (Senger et al, 2005) in brain membranes of zebrafish.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cu had no effect on the monosynaptic excitatory current but reversibly potentiated the disynaptic inhibitory current. This likely reflects disinhibition of interneurons, which express the highest levels of Cu-sensitive, ␣ 1 -subunit-containing GABA A receptors (Kim and Macdonald 2003;. Based on our previous electrophysiological study and the increased sensitivity of PAM ϩ/Ϫ mice to the anxiolytic effects of benzodiazepines (Gaier et al 2010), this result was particularly interesting.…”
Section: Synaptic Effects Of Acute (Bath) Cumentioning
confidence: 92%
“…Further studies have determined that copper inhibits currents in GABA receptors with an IC50 = 2.4  μ M [48]. Copper seems to act in the gating system of the GABA receptor channel [36].…”
Section: Copper As An Essential Metalmentioning
confidence: 99%